Role for a Lytic Polysaccharide Monooxygenase in Cell Wall Remodeling in Streptomyces coelicolor - Xiaobo Zhong; Le Zhang; Gilles P. van Wezel; Erik Vijgenboom; Dennis Claessen (mBio, 2022)
ABSTRACT Peptidoglycan is a major constituent of the bacterial cell wall and an important determinant for providing protection to cells. In addition to peptidoglycan, many bacteria synthesize other glycans that become part of the cell wall. Streptomycetes grow apically, where they synthesize a glycan that is exposed at the outer surface, but how it gets there is unknown. Here, we show that deposition of the apical glycan at the cell surface of Streptomyces coelicolor depends on two key enzymes, the glucanase CslZ and the lytic polysaccharide monooxygenase LpmP. Activity of these enzymes allows localized remodeling and degradation of the peptidoglycan, and we propose that this facilitates passage of the glycan. The absence of both enzymes not only prevents morphological development but also sensitizes strains to lysozyme. Given that lytic polysaccharide monooxygenases are commonly found in microbes, this newly identified biological role in cell wall remodeling may be widespread. IMPORTANCE Lytic polysaccharide monooxygenases are used in industry for the efficient degradation of recalcitrant polysaccharide substrates. Only recently, we have begun to appreciate some of their important biological roles. In this article, we provide evidence that these enzymes are involved in remodeling peptidoglycan, which is a conserved component of the bacterial cell wall. Given that lytic polysaccharide monooxygenases are commonly found in microbes, this newly identified biological role in cell wall remodeling may be widespread.